2022
DOI: 10.3390/biom12010083
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and Diverse Pharmacology of Genus Mimosa: A Review

Abstract: The genus Mimosa belongs to the Fabaceae family and comprises almost 400 species of herbs, shrubs and ornamental trees. The genus Mimosa is found all over the tropics and subtropics of Asia, Africa, South America, North America and Australia. Traditionally, this genus has been popular for the treatment of jaundice, diarrhea, fever, toothache, wound healing, asthma, leprosy, vaginal and urinary complaints, skin diseases, piles, gastrointestinal disorders, small pox, hepatitis, tumor, HIV, ulcers and ringworm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 98 publications
1
18
0
Order By: Relevance
“…In addition, scientific consistency of all medicinal uses is supported by numerous studies highlighting the anticancer [10], antihypertensive, antidiabetic [11], antiinflammatory, antiplasmodial [12], antibacterial [13,14], anti-HIV [15], antiparasitic [16], antioxidant [17,18] and enzyme inhibitory [19,20] properties of extracts and/or secondary metabolites isolated from this plant. Similar broad range of pharmacological activities has been observed with respect to the Mimosa genus [21,22].…”
Section: Introductionsupporting
confidence: 77%
“…In addition, scientific consistency of all medicinal uses is supported by numerous studies highlighting the anticancer [10], antihypertensive, antidiabetic [11], antiinflammatory, antiplasmodial [12], antibacterial [13,14], anti-HIV [15], antiparasitic [16], antioxidant [17,18] and enzyme inhibitory [19,20] properties of extracts and/or secondary metabolites isolated from this plant. Similar broad range of pharmacological activities has been observed with respect to the Mimosa genus [21,22].…”
Section: Introductionsupporting
confidence: 77%
“…A thorough analysis of the literature found that Mimosa pudica contains several marker compounds. e different fractions were found to have varied proportions and composition of constituents [30]. e 14 different chemicals (Figure 3) from the ethyl acetate extract of Mimosa pudica were isolated in a study conducted by Patel and Bhutani [31].…”
Section: Bioactive Compounds In Eamp Through Literaturementioning
confidence: 99%
“…Figure S1: Per-residue energy decomposition of PDE5-APO (Black), PDE5-BUF (Green), PDE5-STI (Yellow), PDE5-ISV (Blue), PDE5-APT (Red) and PDE5-STD drug Sildenafil (Brown). Refs [72][73][74][75][76][77][78] are cited in Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%